Women 4Ps in 4Ps: A Gender Analysis of Philippine Pantawid Pamilyang Pilipino Program - Buan, Richelle Ann C.; Espinosa, Maria Ana E.; Tandayag, Karen Joy P. (Angstrom Centre of Education, 2025)
The Pantawid Pamilyang Pilipino Program (4Ps) was enacted by the Philippine governmentthrough the Republic Act No. 1130 as one of the state’s strategies for extreme povertyalleviation. Patterned after other countries practicing Conditional Cash Transfer Program(CCT), the state provides cash transfer to eligible beneficiaries who must meetconditionalities related to health, education, and nutrition. Even if the program has beenwidely accepted for implementation, it was heavily criticized for being gender blind as itput more burden on the mothers to comply with the requirements compared to othermembers of the family. As key actors who experience the program in its entirety, theresearchers believe that the mother-beneficiaries can offer insights about the program’s realimpact. This paper aims to present a feminist review of 4Ps by problematizing the programas the perceived solution by the Philippine government. The researchers used a modifiedversion of the institutional analysis tool from the Social Relations Framework (SRF), agender analysis approach developed by Naila Kabeer, to examine the varying relationsintertwined in the lives of women beneficiaries under the 4Ps, to wit: people, perception,practice, and power. Moreover, the researchers aim to understand the sense ofempowerment of mother-beneficiaries in the program, and find if the program offers realempowerment for them. Through this study’s analysis and recommendations, powerholders will have the opportunity to rethink the current frameworks used to solve povertyand consider that poverty as intrinsically linked to gender issues.